1998
DOI: 10.1021/jp982772b
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Decomposition of 2,5-Dimethylfuran. Experimental Results and Computer Modeling

Abstract: The thermal reactions of 2,5-dimethylfuran were studied behind reflected shock waves in a pressurized driver single pulse shock tube over the temperature range 1070−1370 K and overall densities of ∼3 × 10-5 mol/cm3. A large number of products resulting from unimolecular cleavage of the ring and consecutive free radical reactions were obtained under shock heating. A methyl group migration from C(2) to C(3) in the ring with the elimination of CO produces four isomers of C5H8 in unimolecular processes. An additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
142
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(150 citation statements)
references
References 23 publications
7
142
0
1
Order By: Relevance
“…Before a potential biofuel should be used in practice, it is advisable to investigate it carefully with respect to its combustion chemistry, including information on the nature and amount of undesired and potentially harmful products. Some of the earlier experimental studies regarding furan fuels have investigated their thermal decomposition [6][7][8][9][10][11][12][13][14][15]. Only a few experiments addressed all three furanic fuels.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Before a potential biofuel should be used in practice, it is advisable to investigate it carefully with respect to its combustion chemistry, including information on the nature and amount of undesired and potentially harmful products. Some of the earlier experimental studies regarding furan fuels have investigated their thermal decomposition [6][7][8][9][10][11][12][13][14][15]. Only a few experiments addressed all three furanic fuels.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few experiments addressed all three furanic fuels. Especially Grela et al [6] employed a heated flow reactor to determine the decomposition rates of furan, 2-methylfuran (MF), and 2,5-dimethylfuran (DMF), and analyzed the pyrolysis products using an online gas chromatography coupled to a mass spectrometer at very low pressure (1.3×10 −3 mbar) and over the temperature range of 1050-1270 K. Also, Lifshitz et al [7][8][9] used shock tube experiments to investigate the thermal decomposition of these three furanic fuels over the temperature range of about 1050 to 1460 K, at pressures of 2 atm. Measurements of the final products were also obtained using gas chromatography techniques, and a chemical kinetic mechanism was proposed to model their results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[58] Ar ecent review by Xu et al [212] presents an overview of available experimental data that may be used for model validation. After some early shock-tube studies,f or example,byLifshitz et al, [213] the first flame measurements of species concentrations were reported in 2011 for furan [172] and tetrahydrofuran. [179] Them ain body of experimental data on the combustion of fuels of the furan and tetrahydrofuran families has been published since 2013, with mechanism development and validation addressed in parallel.…”
Section: Experimental Strategies and Configurationsmentioning
confidence: 99%
“…A large number of experimental studies involved investigations of thermal decomposition in shock tubes and flow reactors [114,[134][135][136][137][138][139][140][141][142][143][144][145][146]. Other studies were aimed at the exploration of rate constants of furan reactions with important radicals during oxidation [20,132,144,[147][148][149][150][151][152].…”
Section: Experimental Chemical Kinetic Studiesmentioning
confidence: 99%